APPLIED LINGUSTICS (GASTRONOMIC STUDY): NAMING, TYPICAL CHARACTERISTICS AND MANUFACTURING TECHNIQUES ON DOCUMENTATION OF TRADITIONAL SNACKS AT PURWOREJO DISTRICT MARKET - Akhmad Mukhibun; Rosantika Utami Setyoningsih (Esteem Journal of English Education Study Programme, 2024)
Traditional foods have names whose origins are unknown. The names of these traditional foods contain meaning, cultural values ​​and history that shape them. This is important to document in order to preserve traditional food and to enrich the formation of Indonesian vocabulary. This research aims to (1) inventory and document Purworejo traditional food in the form of market snacks; (2) describe the meaning of names, characteristics and techniques for making traditional market snacks in Purworejo. This research is qualitative research using a documentation study approach. This research data consists of images, vocabulary and morphological structure. The data source is in the form of documents regarding traditional market snacks in Purworejo Regency. The sampling technique was carried out using purposive sampling. The data collection technique was carried out by document analysis. The data analysis technique is carried out using flowing model data analysis. Testing the validity of the data was carried out by triangulation between researchers. The results of the research showed that (1) 17 names of traditional snacks from Purworejo Regency were found that had not been documented in KBBI V, namely ciwel, clorot, dawet goreng, jenang pati garut/kerut, jongkong, golak, kue lompong, kokrok, putil, legendar, lemet, lupis, mata roda, meniran, rangin, sengkulun, and tahu susur/brontak. (2) The characteristics of each food vary, such as how it is made, how to eat it, and the ingredients used. (3) The making technique is generally done by steaming, boiling and frying. It is hoped that this research can add to the vocabulary of Indonesian and become an effort to preserve traditional Indonesian snacks.